Abnormal glycemic status is common among adults with thyroid dysfunctions (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Abnormal glycemic status and thyroid dysfunctions are the two most common  endocrinopathies. Data regarding glycemic status in Bangladeshi patients with thyroid dysfunctions are  scarce. Objective: This study aimed to see the association of glycemic status among patients with thyroid  dysfunctions. Methods: This cross-sectional study was done among 370 adults with thyroid dysfunctions. Serum thyroid  stimulating hormone and free thyroxine levels were used to categorize the patients with different thyroid  dysfunctions. Fasting plasma glucose for all, two hours after breakfast (2HABF) glucose for previously  diagnosed patients with diabetes mellitus (DM) and 75 gm oral glucose tolerance test (OGTT) were analyzed  by glucose oxidase method. Glycemic status was defined by American Diabetes Association- 2014 guideline. Results: The frequency of hypothyroid, subclinical hypothyroid, euthyroid with levothyroxine, subclinical  hyperthyroidism, and hyperthyroidism participants were 79 (21.35%), 131 (35.41%), 111 (30.0%), 15  (4.05%) and 34 (9.19%) respectively. There were significant differences in the percentages of glycemic status  (p=0.011) among patients with thyroid dysfunctions. The highest percentages of DM and prediabetes were  found among patients with subclinical hyperthyroidism (40.0%) and hyperthyroidism (58.82%) respectively.  A significant association was found between the duration of thyroid dysfunctions with glycemic status  (p=0.037). Conclusions: Glycemic abnormalities are common in patients with thyroid dysfunctions and require regular  screening to prevent mortality and morbidities associated with these combined conditions.J Assoc Clin  Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 04-08